PENGEMBANGAN MEDIA BRAINLY BATTLE BERBASIS KEARIFAN LOKAL PADA MATA PELAJARAN IPAS MATERI SIFAT DAN PERUBAHAN WUJUD BENDA KELAS V SEKOLAH DASAR - Hanif Daffa Praditya; Filia Prima Artharina; Sunan Baedowi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The use of suboptimal learning media has resulted in a low level of student interest and involvement in the learning process. The aim of this study was to determine the validity of local intelligence-based media called Brainly Battle when used on IPAS subjects, in relation to their material characteristics and dynamics of change. Research and Development, or R&D, provides the basis for the models used in these surveys. The only purpose of creating Brainly Battle based learning media is to analyze the effectiveness of learning media in relation to local wisdom. This research was done at SD N 3 Gedong. The evaluation was conducted using the Likert scale examination list of teachers and the Guttman scale form of students, which required a